The Impact of Teaching Strategies on Critical Thinking in Mathematics Education: A Systematic Literature Review - Permatasari, Dinda Agnes; Subanti, Sri; Pramudya, Ikrar; Nurhasanah, Farida (KnE Social Sciences, 2025)
Critical Thinking (CT) is an important skill for students and is one of the most significant indicators of the quality of learning. In the context of mathematics education, CT plays a crucial role as an essential form of thinking. The use of appropriate teaching strategies is essential to develop students’ CT in solving mathematical problems. This research aims to provide a comprehensive overview of the impact of teaching strategies on CT abilities in mathematics education. The research method used is a Systematic Literature Review (SLR) following the PRISMA protocol, which includes reputable databases including Scopus, Eric, Science Direct, and Google Scholar. A total of 916 journal articles have been classified in the identification stage, followed by the screening and eligibility stages, using inclusion and exclusion criteria, as a result, 13 articles were selected for publication in the final stage of the review. The publications considered were between the years 2019 and 2023. The findings of the SLR show that the majority of teaching strategies to enhance CT in mathematics education utilize the problem-based learning (PBL) approach. Furthermore, it can be demonstrated that the majority of the collected studies were conducted at the junior high school level, followed by higher education, senior high school, and primary education levels. Most of the employed teaching strategies have shown significant positive impacts on the development of students’ CT abilities.